1968
DOI: 10.1113/jphysiol.1968.sp008519
|View full text |Cite
|
Sign up to set email alerts
|

The sensations produced by electrical stimulation of the visual cortex

Abstract: 1. An array of radio receivers, connected to electrodes in contact with the occipital pole of the right cerebral hemisphere, has been implanted into a 52‐year‐old blind patient. By giving appropriate radio signals, the patient can be caused to experience sensations of light (‘phosphenes’) in the left half of the visual field. 2. The sensation caused by stimulation through a single electrode is commonly a single very small spot of white light at a constant position in the visual field; but for some electrodes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
642
1
19

Year Published

1968
1968
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,079 publications
(685 citation statements)
references
References 4 publications
23
642
1
19
Order By: Relevance
“…As the spreading oligaemia reaches sensory motor areas of the brain, the patient experiences the focal neurological aura symptoms. The neurological changes during aura parallel what is seen if the brain is directly stimulated (Penfield and Perot, 1963;Brindley and Lewin, 1968) and are also remarkably similar to the changes that would be predicted if ocular dominance columns (Hubel and Weisel, 1968) in the cortex were serially activated. Woods et al (1994) demonstrated a spreading oligaemia directly with a positron emission tomography study.…”
Section: Pathophysiology Of Migrainesupporting
confidence: 66%
“…As the spreading oligaemia reaches sensory motor areas of the brain, the patient experiences the focal neurological aura symptoms. The neurological changes during aura parallel what is seen if the brain is directly stimulated (Penfield and Perot, 1963;Brindley and Lewin, 1968) and are also remarkably similar to the changes that would be predicted if ocular dominance columns (Hubel and Weisel, 1968) in the cortex were serially activated. Woods et al (1994) demonstrated a spreading oligaemia directly with a positron emission tomography study.…”
Section: Pathophysiology Of Migrainesupporting
confidence: 66%
“…Therefore, a sin wave stimulus delivering the same amount of total charge as a square wave stimulus would likely excite a greater population of cells in the electrode center since it does not consist of the higher order harmonics present in the latter. It is interesting to note that early cortical stimulation studies used sin wave stimuli [24], [25], and it has been shown in isolated retina stimulation that sin wave pulses have a lower threshold for stimulation compared with square wave pulses of the same amplitude [26]. …”
Section: Resultsmentioning
confidence: 99%
“…Although early attempts at cortical stimulation in humans used relatively large surface electrodes with high current levels (3,6,24), recent approaches achieved far better results with penetrating microelectrodes terminating in cell body layers. Schmidt et al (25) working in human visual cortex stimulated between single microelectrodes and a remote return and reported pinpoints or disks of light (Ϸ1°maximum).…”
Section: Discussionmentioning
confidence: 99%